Organization and activities of emergency institutions in Crimea in 1921 in conditions of geopolitical tension - A. V. Ishin (Проблемы постсоветского пространства)
The article analyzes the political institutions, processes, technologies characteristic of the period of formation of Soviet power in Crimea after the end of the large-scale Civil War. The phenomenon of the Civil War, from the author’s point of view, was expressed in an irreconcilable struggle between the centers of power that emerged from the ruins of the empire, with the geopolitical factor itself playing an important role. The article notes that in Crimea in 1921, emissaries of British and German intelligence services were actively working, that is, those forces that had previously made considerable efforts to overthrow the monarchy and unleash a Civil War in the Russian Empire. The formation of the Crimean ASSR as part of Soviet Russia in the fall of 1921, as well as the creation of a new powerful state of the USSR with its own social project in December 1922, was not at all part of their plans. Therefore, Western opponents tried as much as possible to use the inertia of the Civil War to destabilize one of the key regions of the RSFSR. Under the current conditions, it was quite logical that a number of leaders of the anti-bolshevik underground wanted to establish close contacts with opponents of Soviet power abroad in order to combine efforts in the fight against it, which objectively became a factor of geopolitical tension in the Soviet Republic in general, and in Crimea in particular. In conditions of increasing conflict in Crimea, a system of emergency institutions is being formed. This system included the Crimean Revolutionary Committee and its local bodies, the establishment of the All-Russian Extraordinary Commission, Special Purpose Units, and revolutionary tribunals under the general ideological leadership of party bodies. The author comes to the conclusion that emergency institutions objectively opposed the implementation of projects of Western powers to destabilize the situation in Crimea and contributed to a certain ethnopolitical stabilization of the situation in the region. On the other hand, their activities were characterized by a class approach, which led to thoughtless repressive policies and inevitable “excesses” in their work, aggravated by weak coordination of actions and the lack of strict control at the first stage.